2021
DOI: 10.3390/cancers13010129
|View full text |Cite
|
Sign up to set email alerts
|

Role of PUM RNA-Binding Proteins in Cancer

Abstract: Until recently, post-transcriptional gene regulation (PTGR), in contrast to transcriptional regulation, was not extensively explored in cancer, even though it seems to be highly important. PUM proteins are well described in the PTGR of several organisms and contain the PUF RNA-binding domain that recognizes the UGUANAUA motif, located mostly in the 3′ untranslated region (3′UTR) of target mRNAs. Depending on the protein cofactors recruited by PUM proteins, target mRNAs are directed towards translation, repress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…Recently, it was reported that mouse Dnd1 is a critical partner of both Nanos2 and Nanos3 proteins in increasing the susceptibility of teratoma formation of PGCs [ 55 ]. Moreover, PUM proteins, one of the best examples of NANOS partner RBPs, were shown to be overexpressed in many types of cancer [ 56 ]. It is likely that the NANOS interactome extends beyond DND1, PUM proteins, and CCR4-NOT deadenylase complexes.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Recently, it was reported that mouse Dnd1 is a critical partner of both Nanos2 and Nanos3 proteins in increasing the susceptibility of teratoma formation of PGCs [ 55 ]. Moreover, PUM proteins, one of the best examples of NANOS partner RBPs, were shown to be overexpressed in many types of cancer [ 56 ]. It is likely that the NANOS interactome extends beyond DND1, PUM proteins, and CCR4-NOT deadenylase complexes.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Additional evidence for post-transcriptional regulatory roles of M17 comes from the analysis of RBP binding sites identified from recently available eCLIP data ( 47 , 48 ) (Figure 2 ). Notable RBPs include the translational repressor and cell proliferation regulator PUM2 and the translational and microRNA-mediated degradation regulators IGF2BP1-3; which could suggest that M17 is involved in regulation of gene expression, cell viability, and localization ( 63–65 ) via modulation of interactions with these regulatory RBPs. Interestingly, four m6A modifications also overlap the RBP interaction sites on M17 (Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…According to the differential correlation analysis of publicly available testis and testicular cancer expression datasets, the NANOS3–PUM1–FOXM1 axis is dysregulated in testis cancer. Previously it was shown that an abnormal expression of NANOS and PUM genes is observed in many types of cancer [ 56 , 57 , 58 , 59 ]. FOXM1 is a critical driver of proliferation and it is overexpressed in a broad range of cancers.…”
Section: Discussionmentioning
confidence: 99%